The evolution of regional capitals in Western Australia: empirical modelling and policy analysis 1984–2014. Issue 3 (2nd September 2017) - Plummer, Paul; McKenzie, Fiona Haslam
ABSTRACT: There is an emerging international academic and policy-oriented literature that draws on economic evolutionary concepts and resilience thinking. Thus far, the design and implementation of resilience thinking appears to run ahead of clarity and rigorous empirical testing. In this article, we attempt to redress this imbalance by employing contemporary economic models and methods to explore the dynamics of four local economies from diverse locations in Western Australia. These localities have been identified as key regional growth centres by the Western Australian State Government. In the broader context, these localities represent a stress test for concepts developed in a different socio-economic context. The evidence shows that these localities lack resilience, displaying path dependence, with external "shocks" having long-run impacts on their developmental trajectories. Furthermore, there is considerable variability between the four centres in their response to shocks, reinforcing political and popular discourse about the existence of a patchwork economy.